Do patient-reported outcome measures for SAH include patient, family, and caregiver priorities?: A scoping review. (5th February 2019) - Saigle, Victoria; Asad, Sarah; Presseau, Justin; Chassé, Michaël; McIntyre, Lauralyn; English, Shane W.
Abstract : Objective: To systematically describe literature that identified patient/family/caregiver priorities for subarachnoid hemorrhage (SAH)–specific patient-reported outcome measures (PROMs), developed novel SAH PROMs by incorporating patient/family/caregiver perspectives, or involved patient/family/caregiver perspectives in evaluating existing SAH PROMs. Methods: We conducted a scoping review using Embase and Ovid MEDLINE from inception to February 6, 2018. Study eligibility and data extraction was performed independently and in duplicate. For each eligible citation, we abstracted information about study population, design, type of patient involvement, and outcome measures. We planned a descriptive summary of all included studies. Results: Our search yielded 4, 961 citations, of which 15 met our eligibility criteria. Four of these included duplicate data, so our final sample consisted of 12 articles. There were 879 patients with SAH and 241 carers from the 11/12 articles that reported these data. One additional study involved 70 individuals but did not specify the number of carers or patients. We did not find any studies where SAH survivors or their families were directly involved in the full continuum of PROM outcome conceptualization from development to evaluation. We found 41 measures identified by patients with SAH. We identified only 2 PROMs developed with patients and only one that was a post hoc evaluation by patients. These 3 PROMs are subarachnoid hemorrhage outcome tool, Wessex Patient Carer Questionnaire, and Functional Status Examination, respectively. Conclusion: We identified 3 PROMs that have involved patients in some way, but the extent to which they reflect patient priorities remains unclear. More work is needed to ensure SAH research is not overlooking outcomes that are important to patients.